Reliability oriented performance evaluation of PV inverter with bifacial panels considering albedos - Sambu, Srikanth; Nayak, Byamakesh (International Journal of Applied Power Engineering (IJAPE), 2024)
The recent advancements in the solar photovoltaic technology is bifacial panels. These panels are capable of producing higher energy than their conventional panels by capturing from both front and rear sides. By harvesting solar energy from both the front and rare surfaces of the panels, the load on the inverters can increase. This affects its reliability performance. Nevertheless, inverter is reported as the critical component in the photovoltaic (PV) system. Hence this work presents reliability-oriented performance evaluation of PV inverter with bifacial panels is proposed. A 3-kilowatt photovoltaic system has been considered with yearly mission profile data at Hyderabad, India. This evaluation is carried out under various albedos. Finally, a comparison between monofacial and bifacial PV panel are presented. The results show that the albedo significantly impacts the lifetime of a PV inverter and therefore, the albedo should be considered when designing a bifacial panel's inverter.